Введение в теорию течения сжимаемой жидкости - Бай Ши-и (Издательство иностранной литературы)
Экземпляры: КХ (20120924) / Инвентарный номер: 314693 / Цена: 1.83 / Сис.шифр: 532 / Авт.знак: Б 18 / ГРНТИ: 29 / ББК: 22